PENINGKATAN SIFAT MEKANIS BESI COR KELABU MELALUI PROSES TEMPERING - A. Noor Setyo HD; Sri Widodo (Journal of Mechanical Engineering, 2018)
This study aims to determine the Hardness and Toughness of cast iron after undergoing a Tempering process with independent variables heating time and dependent Hardness, microstructure and toughness Impack. Quenching was carried out at temperatures of 7750C, 8000C and 8250C in cold water media, while Tempering was carried out at temperatures of 2000C, 3000C and 4000C with a holding time of 15 minutes. Vickers Hardness test results using "Micro Hardness Tester" after Quenching have increased by an average of 95.6% at Quenching 7750C, 99.8% at Quenching 8000C and 107.1% at Quenching temperature 8250C from Hardness value of row material of 256.6 BHN or 260.8 VHN0,040. The maximum hardness value is obtained 531.4 BHN or 553.6 VHN 0,040 at Quenching temperature 8250C and the lowest Hardness of 501.8 BHN or 541,8 VHN0,040 at Quenching 7750C temperature, has Cementite phase as a matrix with little Martensite, is due to treatment The partial tempering of Martensite is replaced by the ferrite phase between Cementites. The results of the study concluded that at Tempering temperatures of 2000C, 3000C and 4000C, the toughness of FC 30 experienced an increase of 106.5%, 121.9% and 130.5% from the initial energy of 5.21 Joule / mm2, whereas violence decreased by 88, 6%, 80.8% and 40.4% of the original Hardness of 260.8 VHN 0,040